2006
DOI: 10.2202/1548-923x.1194
|View full text |Cite
|
Sign up to set email alerts
|

Using Imaginative Literature to Foster Cultural Sensitivity

Abstract: Readings from two novels, Sandra Cisneros' The House on Mango Street and Toni Morrison's The Bluest Eye, were included in maternal-child clinical courses as part of a pilot project to identify potentially effective strategies for increasing student cultural sensitivity and reflective thinking skills. The authors analyzed student journals to determine student values and beliefs during maternal-child clinical experiences. The study sample consisted of 40 young women enrolled in a baccalaureate nursing program in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…ABP seems to alter both the learning process and the learning product (Rieger et al, 2016). There are numerous reported positive outcomes such as self-awareness (Mahar, Iwasiw, & Evans, 2012), awareness of others (Jack, 2012), empathy (Casey, 2009), cultural sensitivity (Newcomb, Cagle, & Walker, 2006), reflection (Jack, 2012), and deeper understanding (Mahar et al, 2012). The emerging body of research suggests that ABP has a meaningful impact on nursing students' development as professionals (Rieger et al, 2016).…”
mentioning
confidence: 99%
“…ABP seems to alter both the learning process and the learning product (Rieger et al, 2016). There are numerous reported positive outcomes such as self-awareness (Mahar, Iwasiw, & Evans, 2012), awareness of others (Jack, 2012), empathy (Casey, 2009), cultural sensitivity (Newcomb, Cagle, & Walker, 2006), reflection (Jack, 2012), and deeper understanding (Mahar et al, 2012). The emerging body of research suggests that ABP has a meaningful impact on nursing students' development as professionals (Rieger et al, 2016).…”
mentioning
confidence: 99%
“…Previous research has demonstrated the utility of the arts in teaching complex and potentially distressing content, such as the destruction of Indigenous culture. Newcomb, Cagle, and Walker (2006) found that through reading imaginative literature, nursing students learned to accept patients with different cultural practices. Begoray and Banister (2008) describe how the use of reading circles helped students learn about Indigenous contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Anderson (2004) has shown that a story from literary journalism can be used to teach cultural awareness and cultural knowledge. Others have used imaginative literature to understand cultural diversity (Halloran, 2009;Newcomb, Cagle, & Walker, 2006).…”
Section: Is It Right To Write?mentioning
confidence: 99%